Expert Perceptual Behavior under the Spatiotemporal Visual Constraints in Table Tennis - Ming-Yuan Tang; Chih-Mei Yang; Hank Jun-Ling Jwo (Asian Society of Kinesiology, 2021)
OBJECTIVES The perceptual ability to detect movement is essential for expert table tennis players. A spatiotemporal occlusion paradigm was employed to examine the critical information that facilitates athletes' perception. METHODS Thirty-one expert table tennis players, 29 participants and 2 demonstrators, volunteered to participate in the study. Four types of temporal conditions and five types of spatial occlusions were displayed in experimental videos of two opponents playing a table tennis forehand stroke. Period t1-4 represented the four temporal conditions, with 250, 500, 750, and 1000 ms of action being occluded, respectively. The five types of spatial occlusion involved showing the kinematics of only the ball, paddle, arm, trunk, or head. The participants were instructed to judge the landing direction of the ball on the basis of the information in the footage. RESULTS The footage depicted the longest period of play. Furthermore, in separate trials, the spatial information (for the ball, torso, or head) was missing because of occlusion. The absence of such critical spatiotemporal information impaired the ability of players to make an accurate prediction. CONCLUSION Players obtained crucial spatiotemporal information if the timeframe of the video was relatively complete and spatial information on the opponent's torso and head was available. For peak performance, expert table tennis players perceive and detect the optical flow of the ball's flight and consider invariant information concerning their opponent's torso and head.